Eccentrically braced steel frames as a seismic force resisting system - Hague, Samuel Dalton (Kansas State University, 2013)
Braced frames are a common seismic lateral force resisting system used in steel structure. Eccentrically braced frames (EBFs) are a relatively new lateral force resisting system developed to resist seismic events in a predictable manner. Properly designed and detailed EBFs behave in a ductile manner through shear or flexural yielding of a link element. The link is created through brace eccentricity with either the column centerlines or the beam midpoint. The ductile yielding produces wide, balanced hysteresis loops, indicating excellent energy dissipation, which is required for high seismic events. This report explains the underlying research of the behavior of EBFs and details the seismic specification used in design. The design process of an EBF is described in detail with design calculations for a 2- and 5-story structure. The design process is from the AISC 341-10 Seismic Provisions for Structural Steel Buildings with the gravity and lateral loads calculated according to ASCE 7-10 Minimum Design Loads for Buildings and Other Structures. Seismic loads are calculated using the Equivalent Lateral Force Procedure. The final member sizes of the 2-story EBF are compared to the results of a study by Eric Grusenmeyer (2012). The results of the parametric study are discussed in detail.
Keywords: Steel; Seismic; Eccentrically braced frame; Lateral force resisting system; Architectural engineering (0462); Civil Engineering (0543); Engineering (0537)